Linear magnet with fluid-solid-switchable cells for flexible devices - Qiyu Deng; Hengjia Zhu; Zhipeng Zhao; Hegeng Li; Ling Yang; Xinya Wu; Yiyuan Zhang; Peng Yu; Xin Tang; Wei Li; Xiaobo Yin; Liqiu Wang (Nature Communications)
Abstract Adjusting magnetization orienting and conformal assembling of high-coercivity micro-magnets at the microscale remains challenging, despite long-standing demand for space-resolved magnetic modulation in various applications. Local magnetic modulation, including remagnetization or reassembly, typically requires high fields and temperatures to overcome the coercivity and stringent conditions while suffering from low assembly efficiency or poor spatial resolution. Here, we report a linear magnet composed of a hydrogel (alginate) matrix and precisely discrete phase-change-material (PCM, eicosane) cells containing micro-magnetic particles (NdFeB, ~5 µm). Moderate local laser heating (~40 °C) reversibly switches PCM from solid to fluid state thus relaxing particles’ interfacial constraints inside the hydrogel matrix, overcoming the high-coercivity of magnetic assembly and allowing particles in cells to reorient under mild fields (≤30 mT). The linear magnet shows excellent discrete magnetization programmability (~150 µm) and stretchability (strain ~80%), enabling versatile functionalities such as conformal and patterned field generation, soft robotic actuation, flexible sensing, and interactive wearables with dynamically coded information.